Perspectives of Indonesian Orthodontists on the Ideal Orthodontic Treatment Time - Al-Gunaid TH; Arifin R; Narmada IB; Tarman KE (Dove Medical Press, 2020)
Talat Hasan Al-Gunaid,1,2 Rafinus Arifin,3 Ida Bagus Narmada,4 Krisnawati E Tarman5 1Department of Pediatric Dentistry and Orthodontics, College of Dentistry, Taibah University, Medina, Kingdom of Saudi Arabia; 2Department of Orthodontics, Faculty of Dentistry, Ibb University, Ibb, Yemen; 3Department of Orthodontics, Faculty of Dental Medicine, Syiah Kuala University, Banda Aceh, Indonesia; 4Department of Orthodontics, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 5Department of Orthodontics, Faculty of Dentistry, University of Indonesia, Jakarta, IndonesiaCorrespondence: Ida Bagus NarmadaDepartment of Orthodontics, Faculty of Dental Medicine, Universitas Airlangga, Surabaya 60132, IndonesiaTel +62315030255Email ida-b-n@fkg.unair.ac.idObjective: The aim of this study was to explore the types of orthodontic treatment provided by Indonesian orthodontists and to analyse their perspectives on the ideal time to initiate orthodontic treatment.Materials and Methods: A cross‑sectional survey was conducted using the Google Drive questionnaire template. This electronic questionnaire was sent to a sample of orthodontists across different regions of Indonesia. The participants were asked to report the stage at which they would start orthodontic treatment, as well as answer questions about occlusal abnormalities and functional problems. Descriptive statistics for all variables were determined, including both practice characteristics and orthodontic treatment timing.Results: A total of 152 orthodontists agreed to participate in the study, of which 64.5% were female and 35.5% were male. Indonesian orthodontists prefer two-phase orthodontic treatment. Sucking habits and open bite were found to be the most frequent indications for treatment in the primary dentition. Anterior crossbite was found to be the most frequent indication for treatment during the early mixed dentition stage. Severe Class II was found to be the most frequent indication for treatment during the late mixed dentition stage. Indonesian orthodontists are more concerned about impacted canines and midline diastema than other occlusal deviations in the permanent dentition.Conclusion: Based on the results of this study, we can conclude that Indonesian orthodontists favor two-phase orthodontic treatment. They also prefer to treat sucking habits and open bite in the primary dentition, anterior crossbite in the early mixed dentition, and severe Class II during the late mixed dentition stage.Keywords: Indonesian orthodontists, orthodontics, treatment timing